Fabrication of novel porous ZIF-67/PES composite microspheres and the efficient adsorption of triphenylmethane dyes from water. Issue 7 (20th January 2023) - Yeerken, Aheyelikai; Lin, Jiangli; Wang, Xiaotian; Luo, Yulu; Ma, Hongying
Abstract : The porous ZIF-67/PES composite microspheres have good MG, FA and CV adsorption performance, which is mainly attributed to π–π superposition between MG, FA and CV and the porous ZIF-67/PES composite microspheres. Abstract : Triphenylmethane dyes not only can be utilized to dye silk, leather, and paper, but they also play an important part in treating parasitic, fungal, and bacterial infections of fish and fish eggs. Although these dyes are inexpensive and have a wide range of applications, they are poisonous. Therefore, their removal from wastewater is crucial for water purification. Metal–organic (MOF)/polymer porous composites were prepared by compounding highly porous MOFs with organic polymers with good stability and hydrophilicity to realize the highly efficient and stable adsorption of triphenylmethane dyes in wastewater over multiple cycles. Porous ZIF-67/PES composite microspheres for the adsorption of triphenylmethane dyes were successfully synthesized via in situ growth, and their adsorption conditions were optimized on the basis of time, pH and NaCl concentrations to investigate their adsorption performance. The as-synthesized porous ZIF-67/PES composite microspheres were characterized by using scanning electron microscopy, X-ray diffractometry, and Fourier transform infrared spectroscopy. Their adsorption kinetics and mechanisms were also studied. Their reusability and stability after cyclic adsorption processes were also investigated. The maximum adsorption capacity of the porous ZIF-67/PES composite microspheres for MG, FA and CV was 5743.28 mg g −1, 2176.52 mg g −1, and 122.78 mg g −1, respectively. Therefore, porous ZIF-67/PES composite microspheres are a potential and efficient absorbent for triarylmethane dye removal.